Introducton to the non-destructive testing of welded joints - Halmshaw, R. (Woodhead Publishing series in welding and other joining technologies., 1996)
This second edition builds on the success of the first and covers the widespread introduction of computer technology, particularly the digitisation of data into the many branches of NDT. It surveys the new European (CEN) Standards and provisional CEN Standards on NDT, many of which are replacing British Standards. New NDT techniques not included in the first edition are also included.